Deferred Prosecution Agreement: Mekanisme Pertanggungjawaban Tindak Pidana Korporasi terhadap Perusakan Lingkungan Melalui Paradigma Restorative Justice - Anindytha Arsa Prameswari; Gerhard Mangara; Rifdah Rudi (Jurnal Hukum Lex Generalis, 2021)
The rise of corporate crime cases has become a major catastrophe for environmental sustainability in Indonesia. However, the trial process takes a long time and it is not oriented towards recovery. Therefore, the authors use a juridical-normative research method to provide a comprehensive description of the Deferred Prosecution Agreement (DPA) with the paradigm of restorative justice and make the implementation of DPA in England and the United States as a benchmark. The implementation of DPA in Indonesia can create an effective and efficient environmental criminal law enforcement.